The Influence of Sabar, Ikhlas, Syukur, and Tawadhu’ on Psychological Well-Being of Multicultural Students in East Kalimantan - Nur Kholik Afandi; Syatria Adymas Pranajaya (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Humans are constantly confronted with a variety of problems, including those pertaining to them as individuals, social beings, and divine beings. These conditions require humans to be always Sabar, Ikhlas, Syukur, and Tawadhu', as the elements of the religiosity dimensions. The population of East Kalimantan is comprised of adolescents with different cultural background enrolled in Junior High School in East Kalimantan. The sampling technique was carried out in phases, beginning with purposive area sampling and concluding with proportional simple random sampling, with a 5% margin of error, using the formula developed by Taro Yamane. Research data collection techniques are observation and questionnaires. SPSS was used to analyze data using multiple linear regression models. Several research findings demonstrate a correlation between religiosity and happiness. This quantitative field study seeks to determine how the attitudes of Sabar, Syukur, Ikhlas, and Tawadhu' influence the psychological well-being of East Kalimantan students. The coefficient of determination of 0.668 indicates that Ikhlas (X2), Syukur (X3), and Tawadhu' (X4) directly influence the Y variable by 66.8%, while the remaining (100-60)% = 33.2% is influenced by other factors in addition to Sabar (X1), Ikhlas (X2), Syukur (X3), and Tawadhu' (X4) that were not included in this study. On the basis of these considerations, the research findings can serve as a guide for educational curriculum stakeholders conducting research on the policy, theory, and practice of educational curricula containing the variables Sabar, Ikhlas, Syukur, and Tawadhu' in order to enhance the psychological well-being of students.